Bacterial ecology of tilapia fresh fillets and some factors that can influence their microbial quality - Boari,Cleube Andrade (2008)
The purpose of research was to investigate the bacterial ecology of tilapia (Oreochromis niloticus) fresh fillets and some factors that can influence its microbial quality. Samples of fish cultivation water (n = 20), tilapia tegument and gut (n = 20) and fresh fillets (n = 20) were collected in an experimental tilapia aquaculture located in the city of Lavras, Minas Gerais, Brazil. Staphylococcus spp., Aeromonas spp., Enterococcus spp. and Enterobacteriaceae were quantified using selective plating. For the enumeration of Pseudomonas spp., the most probable number technique (MPN) was utilized. Bacterial colonies (n = 198) were identified by Gram strain and biochemical tests. Aeromonas spp., Pseudomonas spp., Enterococcus spp. and Enterobacteriaceae were found in the cultivation water (water from a fishpond cultivation), tegument, gut, and fresh fillets. Staphylococcus spp. was not isolated in the cultivation water. Salmonella spp. was not detected. The count variable of 10 to 10³ CFU or MPN.(g or mL)-1. Associated to freshwater tilapia fillet processing, there is a large variety of microorganisms related to foodborne illnesses and fish products deterioration.